2012
DOI: 10.21608/egyjnm.2012.5483
|View full text |Cite
|
Sign up to set email alerts
|

Successful Complete Ablation Rate Post a Second Ablation Dose of 30 mCi Radioactive Iodine (I131) in Patients with Papillary Thyroid Cancer

Abstract: Conclusion:The successful complete ablation rate after a second ablation dose of is higher than first ablation dose of 100 mCi 1131. No significant difference between completely and non-completely ablated patients after the second ablation dose (30 mCi) as regards age, gender and histopathological details.The overall complete ablation rate after 130 mCi is 90%, this figure is significantly higher than the same figure post either first or second ablation dose separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
0
1
Order By: Relevance
“…These figures are comparable to our previous report of 72% response to a second ablation dose of 30 mCi (1110 MBq) [18]. These figures are comparable to our previous report of 72% response to a second ablation dose of 30 mCi (1110 MBq) [18].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These figures are comparable to our previous report of 72% response to a second ablation dose of 30 mCi (1110 MBq) [18]. These figures are comparable to our previous report of 72% response to a second ablation dose of 30 mCi (1110 MBq) [18].…”
Section: Discussionsupporting
confidence: 89%
“…However, they reported that the application of high doses is significantly more effective in thyroid remnant ablation compared with the administration of low doses. In our experience, our group reported in 2012 an ablation outcome of 64% after a first dose of 3700 MBq [18], whereas in the current study the second 131 I application had an overall successful outcome of 75%. In our experience, our group reported in 2012 an ablation outcome of 64% after a first dose of 3700 MBq [18], whereas in the current study the second 131 I application had an overall successful outcome of 75%.…”
Section: Discussioncontrasting
confidence: 54%